Did the Economic Reforms Change the Macroeconomic Drivers of the Indian Economy in the Post-Reform Era? An ARDL Bounds Test Approach - REDDY, Pujari Sudharsana; BAGRECHA, Chaya; KRISHNAN, Muthu Gopala (Theoretical and Practical Research in Economic Fields, 2023)
Purpose:  The purpose of this study is to investigate the macroeconomic forces that have been driving the Indian economy during both the pre-reform and post-reform eras, that is, from 1950-1951 to 1990-1991 and from 1991-1992 to 2022-2023 respectively.  Problem:  The Indian economy underwent significant economic and financial sector reforms in 1991-92, with the goal of reviving its stagnant growth.  These reforms are intended to spur the economic growth of India.  What were the main forces behind the Indian economy before and after the reforms? Is the research question.  The goal of the current study is to determine if the economic reforms shifted or maintained the pre-reform era’s driving forces for the Indian economy in the post-reform era.  Design/Methodology/Approach:  The gross domestic product (GDP), the gross domestic savings (GDS), the private consumption expenditure (PFCE), the government final consumption expenditure (GFCE),  the inflation rate, the exchange rate, the exports, the imports, the internal and external borrowings of the government, personal remittances, foreign direct investment (FDI), and foreign portfolio investments (FPI) are all taken into consideration in order to fill the research gap that has been identified as a result of the comprehensive review of the literature.  Following an analysis of the selected variables' fundamental characteristics, an econometric model is developed using the Autoregressive Distributed Lag (ARDL) Bounds Test Model.  Findings: There is no evidence of long-run causation and association between the variables, but the findings of the ARDL Bounds Test showed that in the pre-reform period, PFCE is the major driver of the GDP in the short-run, with strong support from imports.  However, since the reform, PFCE, GDS, and Exports are the primary short- and long-term contributors to GDP.  Practical Implication: These findings indicate that India's macroeconomic system is shifting.  The Indian economy has undergone a dramatic shift, moving away from a reliance on imports and toward one that is consumer-driven and export-driven. As savings and consumer expenditures are the main drivers of the Indian economy’s growth in the post-reform era, policies should be designed to increase savings and consumption as well as increase exports.